Reflexões sobre a variação terminológica na lexicografia corrente no Brasil e a construção das bases teórico-metodológicas para o dicionário de lexicografia brasileira - Costa, Lucimara Alves da Conceição [UNESP] (2015)
This research aims at reflecting on the phenomenon of terminological variation in use in Lexicography, in Brazil. Relying on the premise of the Communicative Theory of Terminology (CTT), we understand that the terms, as units inserted in a specialized context and discourse, are mutable and prone to variation, both in terms of denomination (denominative variation), and concept (conceptual variation). However, our study focuses only on the denominative variation with and without cognitive consequences. In order to analyze the data, we have built a specialized corpus constituted of 300 texts, with varying typology in the domain of Lexicography, written in Brazilian Portuguese. By resorting to computational softwares such as Wordsmith Tools and Terminus, it was feasible to retrieve eligible terms in our corpus, and select their defining contexts and analyze how the phenomenon of variation unfolds. Lastly, we organized and showed the obtained information as a proposal for a Dictionary of Brazilian Lexicography - DBL -, which aims at showing a macro and microstructural organization as a resource for comprehension, production and communication activities of a target audience made up of students and experts in this field of study.